1996
DOI: 10.1016/0005-2728(96)00051-5
|View full text |Cite
|
Sign up to set email alerts
|

A compilation of mutations located in the cytochrome b subunit of the bacterial and mitochondrial bc1 complex

Abstract: In anticipation of the structure of the bc1 complex which is now imminent, we present here a preliminary compilation of all available cytochrome b mutants that have been isolated or constructed to date both in prokaryotic and eukaryotic species. We have briefly summarized their salient properties with respect to the structure and function of cytochrome b and to the Qo and Qi sites of the bc1 complex. In conjunction with the high resolution structure of the bc1 complex, this database is expected to serve as a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
134
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(145 citation statements)
references
References 34 publications
10
134
0
1
Order By: Relevance
“…Y132F QCR exhibits unchanged sensitivity to stigmatellin but is resistant to myxothiazol (Table 1). This agrees with results obtained for the equivalent mutation in bacterial QCR (9). Each of the substitutions in position 279 altered the sensitivity for both inhibitors.…”
Section: Thesupporting
confidence: 90%
See 1 more Smart Citation
“…Y132F QCR exhibits unchanged sensitivity to stigmatellin but is resistant to myxothiazol (Table 1). This agrees with results obtained for the equivalent mutation in bacterial QCR (9). Each of the substitutions in position 279 altered the sensitivity for both inhibitors.…”
Section: Thesupporting
confidence: 90%
“…This residue is a locus of center P inhibitor resistance both in yeast and bacterial QCR (17)(18)(19). Mutational analysis of the equivalent residue in bacterial QCR (Phe 144 ) indicated that replacement of Phe 144 affects ubiquinol binding and oxidation (9). The residue Tyr 279 is close to the highly conserved PEWY (Pro 271 -Tyr 274 ) motif, and it has been suggested to take part in positioning ubiquinol prior to oxidation and in stabilizing the enzyme-substrate complex by weak hydrogen bonds (6).…”
Section: /Ementioning
confidence: 99%
“…Glu-295 in cytochrome b is important for the release of the second proton, as proposed previously (31)(32)(33). Glu-295 is completely conserved in mitochondrial cytochrome b (34), and the importance of the residue in proton transfer is indicated by mutagenesis studies because alteration of glutamine abolishes ubiquinol oxidation in R. sphaeroides (35). Additionally, recent kinetic studies showed that protonation of a group with a pK a of 5.7 blocked catalysis, and this effect was attributed to Glu-295 (36).…”
Section: Photosynthetic Growth Behaviors Of the Wild-type Andsupporting
confidence: 53%
“…Spans contributing to the site include the C-terminal end of the transmembrane helix C (blue in Figure 2, middle), the cd1 helix (green-blue), the ef loop, including a coil from the end of the helix E (green), the -PEWY-turn (yellow), the small ef helix (orange) connecting the -PEWY-turn to transmembrane helix F, and the N-terminal end of helix F (red). These contributions had been predicted from model building based on sequence analysis and the sites at which inhibitor-resistant lesions had been identified or at which changes in function had been generated by specific mutagenesis (26,(35)(36)(37).…”
Section: Positionsmentioning
confidence: 99%